1303. Provider Knowledge and Attitudes Toward Antibiotic Prescribing and Antibiotic Stewardship in Outpatient Rural Clinics. (26th November 2018) - Kufel, Wesley; Mogle, Bryan; Williams, Karen; Jester, James; Snyder, John; Mastro, Keri; Lubowski, Theresa; Bohan, KarenBeth
Abstract: Background: Rural outpatient clinics serve the healthcare needs of many individuals, especially for acute sick visits and infectious processes. A better understanding of providers' knowledge and attitudes toward antibiotic stewardship in the outpatient rural setting is needed to facilitate more effective education regarding appropriate antibiotic prescribing. Methods: A cross-sectional, multi-center, 28-item survey assessing providers' knowledge and attitudes toward antibiotic prescribing and antibiotic stewardship in the rural setting was distributed to providers from Guthrie and United Health Services primary care clinics in rural New York and Pennsylvania. Results: Sixty-five providers participated (31% response rate) with 43%, 29%, and 28% of responses from physicians, resident physicians, and advanced practice providers, respectively. More than half of respondents practiced for ≤5 years since terminal training. The most significant barrier to improving antibiotic prescribing was patient demands (55%) followed by uncertain diagnosis of bacterial infection (22%) and short appointment visit times (11%). Providers that spent ≤20 minutes per visit were more likely to feel pressured to prescribe antibiotics for upper respiratory tract infections (URI) to ensure patient satisfaction than those who spent >20 minutes (41% vs. 7%, P = 0.024). Additionally, providers who saw >50 patients per week were more likely to feel pressured to prescribe antibiotics for URIs than those who saw ≤50 patients (50% vs. 18%, P = 0.009). Only 42% of providers selected the correct answer that 90–98% of URIs are viral. The majority of providers strongly agreed that antibiotics are overused (71%) and inappropriate antibiotic use can lead to resistance (82%). Thirty-eight percent of providers never heard the term antibiotic stewardship or heard the term but were unsure about the definition. However, more than 75% of providers strongly agreed or agreed that they were interested in receiving more education regarding antibiotic stewardship. Conclusion: Variability exists among providers' knowledge and attitudes toward antibiotic stewardship and antibiotic prescribing in rural outpatient settings. Increased educational efforts are warranted to increase consistency of these concepts and practices. Disclosures: All authors: No reported disclosures.